Faktor-Faktor Yang Berhubungan Dengan Kejadian Kecacingan Soil Transmitted Helminths Pada Anak Usia 1 – 5 Tahun Di Rw 07 Geringging Kecamatan Rumbai Pesisir - Sri Kartini; Ilham Kurniati; Nandriya Safarin Jayati; Windra Sumitra (JURNAL FARMASI DAN MAKANAN, 2017)
Helminthiasis is a disease that occurs in the population in the tropics and subtropics area.One of the helminthiasis in humans is Soil Transmitted Helminth (STH). The prevalence of this disease is still to be a concern because the prevalence is quite high in children that is no exception in the children aged 1-5 years. The factors causing helminthiasis are included behavioral and environmental factors. This study aims to determine the factors that are related to STH helminthiasis incidence among others, the habit of washing hand of mothers, the habit of wearing footwear, the cleanliness of mother and child's nails, the availability of clean water, the availability of latrines and the availability of the trash. The sample is the total population of 55 children aged 1-5 years in RW 07 Geringging Rumbai Pesisir District. This research is an observational quantitative with cross sectional design.Data is taken from the result of questionnaire and human fecal sample. The data were analyzed using chi square test. The result of the research showing STH infected children were 7 people (12,7%). The types of the worm eggs that infect are Ascaris lumbricoides (7.2%), Trichuris trichiura (3.6%), and hookworm (1.8%). The result of statistical test showed that there was a relationship between hand washing habits (p = 0,039), children habit wearing footwear (p = 0,002), clean of mother and child nail (p = 0,041), clean water supply (p = 0,016) (p = 0,024) and there is no relation between garbage availability (p = 0,168)) to the occurrence of helminthiasis. Keywords: Helminthiasis, washing hand of mothers, wearing children's footwear, cleaning mother's and children's nails, availability of clean water, availability of latrines